18 month-old growth performance of four selected Acacia species provenance trial - Senin, Abdul Latib; Ab Shukor, Nor Aini; Abdul Hamid, Hazandy; Awang, Kamis (Forest Research Institute Malaysia, 2007)

(untitled)
Assessment of growth performance of selected Acacia species viz., Acacia mangium Willd, A. crassicarpa A. Cunn. ex Benth, A. auriculiformis A. Cunn. ex Benth. and A. aulacocarpa A. Cunn. ex Benth. was conducted. The field trial was established at Aur Gading, Kuala Lipis Pahang using a completely randomized block design (RCBD) with four replications of four provenances each. The materials used were from the Papua New Guinea and Queensland regions. Assessments of survival and growth performance were undertaken after 18 months. Significant differences at p < 0.05 were obtained between species, provenances and regions for survival, height and dbh. Generally, materials from PNG region were superior to QLD sources. Among the four species, A. mangium was found to be the most outstanding with its potential provenances from SW of Boset WP (PNG) and Bensbach WP (PNG). The findings of this study suggested that variation between species, provenances and regions are important estimates or criteria of selection for appropriate sources to be used in tree improvement and breeding programmes on sites that share similar environmental conditions.